Effects of Hyaluronic Acid on Three Different Cell Types of the Periodontium in a Novel Multi-Culture Cell Plate: An Exploratory Study - Alessio Barbieri; Luciano Pitzurra; Bruno Loos; Ineke D. C. Jansen (Biomolecules)
Hyaluronic acid (HA) has received considerable attention in the reconstruction of lost periodontal tissues. HA has been proposed to play a role in cell proliferation, differentiation, migration, and cell–matrix as well as cell–cell interactions. Although various studies have been conducted, further research is needed to expand our knowledge based on HA such as its effects on cell proliferation and osteogenic differentiation. The aim of this study is to assess, in single- and multi-culture plate models, the effect of HA on the proliferation, viability, and function of periodontal ligament fibroblasts, osteoblasts, and gingival epithelial cells. A novel multi-culture cell plate was chosen to simulate a cell–cell communication as close as possible to a real clinical condition in an in vitro setting. We found that HA exclusively enhanced epithelial cell proliferation, while intercellular communication stimulated the proliferation and osteogenic potential of the osteoblasts, independently from HA use. The proliferation and function of the periodontal ligament fibroblasts were not changed by HA or the cellular interplay. The use of multi-culture plates could represent a promising method to investigate and compare dental biomaterials in experiments mimicking an in vivo environment.